Analysis of the use of different resources in a didactic website - Francisco Cabello Luque; Ana Vanesa Valero García (Universidad de Málaga, 2019)
To analyze how students use online learning tools, such as didactic websites, a common practice is to report global access statistics. Although these are adequate measures, they are not specific enough and do not allow to determine if there are differences depending on the type of resources available to students. The aim of this study is to compare how students use different types of resources in a didactic website, distinguishing between resources to be evaluated in a final exam, resources for work in the classroom, extension resources not to be evaluated, and online extension resources. To this end, the 96 students (87 women, 9 men) taking part in the research enrolled in a subject that is part of the Degree in Speech Therapy, and where a didactic website was used as a tool to complement face-to-face teaching. The total number of accesses to the didactic website and the average number of reads of each type of resources were taken as units of measure. The results indicated that, although the number of visits generally reflected an intense, frequent, stable use of the website, at the same time there were some types of resources that were hardly used by students. Thus, it is suggested that the availability of a particular learning resource on a didactic website does not imply that it will be used, and that the best way to increase the use of a resource is to evaluate it, or to use it in the classroom.